2020
DOI: 10.3892/ol.2020.11935
|View full text |Cite
|
Sign up to set email alerts
|

miR‑642 serves as a tumor suppressor in hepatocellular carcinoma by regulating SEMA4C and p38 MAPK signaling pathway

Abstract: Hepatocellular carcinoma (HCC) is a malignant tumor with high incidence and high risk. Study of the role and mechanism of miRNAs are a hot spot of research providing new treatment ideas in malignant tumors. The effect of miR-642a on HCC progression and the underlying molecular mechanism were investigated. Expression of miR-642a and SEMA4C was measured by western blot analysis and RT-PCR. miR-642a expression was elevated while SEMA4C expression was attenuated in HCC tissues and cells. Results of luciferase repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Based on the expression pattern of miR-136-5p in HCC, its interacted mRNAs should exhibit high expression in HCC. Through bioinformatics prediction and literature review, we focused on six candidate mRNAs, including PAX6 [ 29 ], SEMA4C [ 30 ], ROCK1 [ 31 ], FZD4 [ 32 ], TRIM27 [ 20 ], and ABCC12 [ 33 ]. MiR-136-5p overexpression reduced the levels of FZD4, TRIM27, and ABCC12 in both HCC cell lines ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the expression pattern of miR-136-5p in HCC, its interacted mRNAs should exhibit high expression in HCC. Through bioinformatics prediction and literature review, we focused on six candidate mRNAs, including PAX6 [ 29 ], SEMA4C [ 30 ], ROCK1 [ 31 ], FZD4 [ 32 ], TRIM27 [ 20 ], and ABCC12 [ 33 ]. MiR-136-5p overexpression reduced the levels of FZD4, TRIM27, and ABCC12 in both HCC cell lines ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…miRNA-642 downregulation reduced the cell viability in bladder cancer cell lines, with different cisplatin sensitivity [ 27 ]. It was described recently that miRNA-642 could act as a tumor suppressor through regulating p38 MAPK signaling pathway in hepatocellular carcinoma [ 28 ]. In addition, miRNA-642 served as a tumor suppressor in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, women with obesity are at increased risk of breast cancers, therefore, differentially expressed miRNAs of bEVs in mothers with obesity could be the molecules that either help us to predict breast cancer occurrence or trigger cancer development. In fact, previous studies demonstrated that downregulated miRNAs in bEV of mothers with obesity, such as miR-630 and miR-642 , suppress cancers ( 61 , 62 ). miR-548j-3p , upregulated in mothers with obesity, plays a role as a metastasis promoter in breast cancer ( 63 ).…”
Section: Discussionmentioning
confidence: 99%